ABOUT POSSIBILITY OF SELECTIVE MODIFYING OF QUICK-SPEED STEEL - F. I. Rudnitsky; Yu. A. Nikolaychik; A. N. Yermak (Литьë и металлургия, 2014)
It is established that in spite of presence of tungsten in composition of high-speed steel P6M5 at additional introduction of this element in volume of 0,1-0,6% the selective modifying effect becomes apparent.